2022
DOI: 10.1136/bmjopen-2020-047868
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on the utilisation of health services at public hospitals in Yemen: a retrospective comparative study

Abstract: BackgroundThe COVID-19 pandemic has led to a global crisis, creating an unprecedented situation, which has taken the world by storm, overshadowing on all life’ aspects and having a significant impact on the health systems of most countries. In this study, the delivery of health services is investigated both before and during the outbreak of the COVID-19 pandemic at public hospitals in Yemen to assess the impact of COVID-19 on the utilisation of health services.MethodData collected from 127 hospitals in Yemen w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 24 publications
4
19
0
Order By: Relevance
“…The ndings of this study reveal that slightly less than half of the respondents did not use healthcare services during the COVID-19 period. This nding is consistent with other studies that reported a reduction in health care utilization especially at the beginning of the pandemic [17][18][19][20][21]. This reduction in healthcare utilization can be partially explained by the limited mobility of the UAE population during the entire lockdown period that was imposed by the government.…”
Section: Discussionsupporting
confidence: 92%
“…The ndings of this study reveal that slightly less than half of the respondents did not use healthcare services during the COVID-19 period. This nding is consistent with other studies that reported a reduction in health care utilization especially at the beginning of the pandemic [17][18][19][20][21]. This reduction in healthcare utilization can be partially explained by the limited mobility of the UAE population during the entire lockdown period that was imposed by the government.…”
Section: Discussionsupporting
confidence: 92%
“…In countries, the approach mitigated reporting burden and fostered cross-programme discussions, by offering one coordinated and comprehensive tool to assess different service areas. Moreover, to the extent that validation has been possible, the findings have echoed other studies that found consistent but variable impacts on essential health services across health domains ( 4 , 5 , 69 – 73 ).…”
Section: Discussionsupporting
confidence: 69%
“…The maintenance of essential health services during the corona virus disease of 2019 (COVID-19) pandemic has been critical, as disruptions to essential health services-including for health promotion, disease prevention, diagnosis, treatment, rehabilitation, and palliation-may lead to even greater adverse health outcomes than the pandemic itself, especially in vulnerable populations (1)(2)(3)(4)(5)(6)(7). However, throughout the pandemic, many countries have faced complex challenges that required accurate and timely data on facility capacities, service utilization, and community needs and preferences to inform the development of action plans and strategies to respond to COVID-19 while maintaining safe delivery of care.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent study from UK found that health service utilization decreased by 70% and respiratory system disease treatment services by 42% during the first wave of the pandemic. ( 9 ) Another study in Yemen reported a 10% reduction in surgery and a 4% decrease in medical consultation during the early phase of the pandemic in 2020 ( 16 ). Similar trends were observed in other countries, such as Armenia ( 17 ), Iran ( 18 ), and Italy ( 19 ).…”
Section: Discussionmentioning
confidence: 99%